Biden's Policy towards the Palestinian-Israeli conflict Opportunities for change and limits of influence - ALsardi, Ali Fahhad (Dirasat: Human and Social Sciences, 2025)
Objective: Analyzing Biden's policy towards the Palestinian-Israeli conflict by linking it to various variables to determine the extent to which it motivates Biden's policy to respond to the requirements of managing this conflict towards a political settlement. Methods: Analyzing Biden's policy objectively, considering its connection to various variables, relying on the deductive, descriptive, and comparative approaches, aiming to answer the study's problem questions and test hypotheses that stem from the relationship between the Palestinian-Israeli conflict and multiple dependent variables. Results: Biden's policy has remained bound by Trump's decisions, demonstrating a steadfast commitment to Israel's security, as evidenced by his stance on the “Al-Aqsa Flood”. Conclusion: The Biden administration has reverted to managing the Palestinian-Israeli conflict driven by a set of variables in the region, but its policy towards this conflict has remained captive to Trump's decisions and his vision for its resolution. Consequently, Biden's policy has bolstered Israel's gains and security at the expense of the rights and demands of the Palestinian people.